Protest in South Africa: motives and meanings. Issue 5 (28th July 2016) - Lodge, Tom; Mottiar, Shauna
Abstract : South Africa is experiencing record levels of protest. Interpretations of protest fall into two groups. First, there is the argument that protests represent only limited rebellion and that though unruly, they are a mechanism for political re-engagement. A second understanding links "new social movements" that address general grievances to wider hegemonic challenges. This article addresses the issue of whether these upsurges in militant mobilization threaten or complement democratic procedures. The article draws from a study of two protest "hotspots" in Durban.